Bentham and the Arts - Julius, Anthony; Quinn, Malcolm; Schofield, Philip (UCL Press, 2020)
Bentham and the Arts considers the sceptical challenge presented by Bentham's hedonistic utilitarianism to the existence of the aesthetic, as represented in the oft-quoted statement that, 'Prejudice apart, the game of push-pin is of equal value with the arts and sciences of music and poetry. If the game of push-pin furnish more pleasure, it is more valuable than either.' This statement is one part of a complex set of arguments on culture, taste, and utility that Bentham pursued over his lifetime, in which sensations of pleasure and pain were opposed to aesthetic sensibility. Leading scholars from a variety of disciplines reflect on the implications of Bentham's radical utilitarian approach for our understanding of the history and contemporary nature of art, literature, and aesthetics more generally. Each contributor takes into account, from the perspective of their own discipline and expertise, the implications for their research area of the views contained in Bentham's Of Sexual Irregularities, and other writings on Sexual Morality (published in the authoritative edition of The Collected Works of Jeremy Bentham in 2014) and 'Not Paul, but Jesus: Volume III' (published online by the Bentham Project in 2014). In these essays, Bentham puts forward the first philosophical defence of sexual liberty. In doing so, he questions the meaning of 'taste' and hence the received understanding of aesthetics more generally. The contributors, moreover, challenge two of the major commonplaces in literary and historical studies of the nineteenth century: first that literature and utilitarianism represented alternative and incompatible views of the world; and second that Bentham's utilitarianism was somehow emaciated in comparison with that of John Stuart Mill. The volume also includes new reflections on the auto-icon and the panopticon, the latter showing the utilitarian genealogy of a collaborative art and architecture project on the site of the Millbank Penitentiary. The title 'Bentham and the Arts' itself challenges the commonly held notion that Bentham had nothing relevant to say on the subject of the Arts - the essays in this volume show that Bentham remains extraordinarily relevant, both in historical and philosophical terms. 'Bentham and the Arts is a feast. Ranging from poetry and sexual nonconformity to the auto-icon and public sculpture, from Hume, Kant, and de Staël to Freud and Michel Onfray, an excellent crew of contributors brings Jeremy Bentham out from the shadow cast by John Stuart Mill with much new to say on taste and politics. Highly recommended for students and scholars alike, this fine interdisciplinary volume is available to all through open-access publishing.' - Stephen Engelmann, University of Illinois at Chicago